Numerical prediction of ducted propeller performance based on a BEM–RANS coupling method. (1st March 2023) - Jin, Zhihui; Wang, Peng; Dong, Huachao; An, Xiaoyi; Xia, Hui
Abstract: This paper presents a coupling method that combines the boundary element method (BEM) and the Reynolds-averaged Navier–Stokes (RANS) method to calculate the ducted propeller performance. The software ANSYS CFX is primarily used to calculate the viscous flow around the duct considering the action of the propeller through the distribution of body forces, and the performance of the propeller is evaluated using the BEM in the effective inflow field. A conservative interpolation scheme that converts the pressure obtained from the BEM into the body force of the RANS solver is described. Then, a Kriging interpolation method is used to determine the effective wake by combining the total viscous field and induced velocities from the BEM. Compared with a full RANS approach, this coupling method allows for investigation of the interaction between the duct and propeller with a significantly reduced computational effort and ensures accuracy with a smaller number of meshes. In addition, the coupling method provides a significant effective wake field for propeller design. The proposed coupling method is first applied to the case of an open propeller and is then assessed for the case of a ducted propeller under uniform flow. The results show that the proposed coupling method provides similar prediction results as those obtained using the full RANS approach, with a 79.6% reduction in computational time. Highlights: A BEM-RANS coupling method for calculating ducted propeller performance is presented. The BEM-RANS coupling method is applied to the KP505 propeller and the Ka4-70 propeller operating in a 19A duct. A conservative interpolation scheme converts the pressure obtained from the BEM to the body force of RANS solver. A strategy of equivalent radius is improved to deal with higher mesh density for the gap between the blade tip and duct. The effective wakes are predicted in different upstream surfaces to assess the impact on the inflow.